Motivasi dan Minat Mahasiswa PBA FAI UHAMKA Mengajar di Sekolah Persyarikatan Muhammadiyah - Ahmad Rizki Nugrahawan; Yoan Pratama (Riyahuna: Jurnal Pendidikan Bahasa Arab, 2021)
This study aims to analyze the motivation and interest in teaching students of the UHAMKA Arabic Language Education Study Program at the Persyarikatan Muhammadiyah school. This research method uses quantitative methods with qualitative descriptive. The main object of this research is the 6th and 8th semester students. The results obtained are 78.8%, the majority of students start their intentions from themselves. The motivation to become a teacher is also very large (63.5%), Based on Physiological Needs (Physiological Needs), Personal Intentions and ideals (65.4%), Based on Safety needs (Security needs, namely a healthy and wise work environment (90.4 %). Based on Belongingness and Love needs (the need to have and love), the totality due to the possessing factor, namely (94%). Based on Esteem needs (needs for self-esteem), prestige (50%) Based on Self-Actualization needs (Needs for self-actualization), has the ability to teach (92.2%), a sense of belonging and love for Muhammadiyah is normal (53.8%). The motivation to become a teacher at the Persyarikatan Muhammadiyah School is as a dedication to the Muhammadiyah organization (51.9%), The need to become a teacher at the Persyarikatan Muhammadiyah School is as self-development (71.4%). iyah and other schools, namely Muhammadiyah persyarikatan schools (50%), the choice in difficult conditions when teaching at Muhammadiyah Persyarikatan Schools or at other schools, namely to persist and try to help until things return to normal (82.7%).